Records management practices in institutions of higher learning in South Africa- : a case of University of Venda - Singo, Geven (My University, 2024)
This qualitative study aimed to explore the records management practices at the University of Venda in South Africa. An interpretivist philosophy guided the study to understand subjective experiences of records management staff. Case study approach was used to gain in-depth insights into the University’s records management. The study used qualitative semi-structured interviews and thematic analysis. Ten purposively selected records management personnel participated. Primary data were collected through in-depth, face-to-face interviews. Interview transcripts were thematically analysed using NVivo software. Key findings were that records management practices are inconsistent across the University due to gaps in oversight; a continued dependence on paper records was also found, though digital growth is acknowledged; perspectives on the benefits of records management varied among staff; inadequate infrastructure and systems pose major challenges; legal compliance ambiguities persist across departments; and poor record accessibility and retrieval hamper operations. Recommendations made were to develop a comprehensive records management strategy and electronic records system; provide extensive training programmes to build expertise; establish centralised governance to coordinate practices; conduct regular audits for monitoring and compliance; and formulate policies for consistency in records management. In summary, the study revealed substantial deficiencies in records management practices compared to standards and provides evidence-based recommendations focused on strategy, technology, training, governance and auditing to modernise and strengthen records management across the University.
Thesis (M. (Information Studies)) -- University of Limpopo, 2024
Keywords: Records management practices; Institution of higher learning; University of Venda; Records retention; Education, Higher -- South Africa -- Limpopo